Computational Derivation of Core, Dynamic Human Blunt Trauma Inflammatory Endotypes - Schimunek, Lukas; Lindberg, Haley; Cohen, Maria; Namas, Rami A.; Mi, Qi; Yin, Jinling; Barclay, Derek; El-Dehaibi, Fayten; Abboud, Andrew; Zamora, Ruben; Billiar, Timothy Robert; Vodovotz, Yoram (Frontiers in Immunology, 2021)
Systemic inflammation ensues following traumatic injury, driving immune dysregulation and multiple organ dysfunction (MOD). While a balanced immune/inflammatory response is ideal for promoting tissue regeneration, most trauma patients exhibit variable and either overly exuberant or overly damped responses that likely drive adverse clinical outcomes. Using Patient-Specific Principal Component Analysis followed by unsupervised hierarchical clustering of circulating inflammatory mediators obtained in the first 24 h after injury, we segregated a cohort of 227 blunt trauma survivors into three core endotypes exhibiting significant differences in requirement for mechanical ventilation, duration of ventilation, and MOD over 7 days. Nine non-survivors co-segregated with survivors. Dynamic network inference, Fisher Score analysis, and correlations of IL-17A with GM-CSF/IL-10 in the three survivor sub-groups suggested a role for type 3 immunity, in part regulated by Th17 cells, and related tissue-protective cytokines as a key feature of systemic inflammation following injury. These endotypes may represent archetypal adaptive, over-exuberant, and overly damped inflammatory responses.